Perluasan Jaringan Internet Nirkabel dan Penyediaan Sarana TIK untuk Mendukung Pengembangan Kampung Digital di KIM NAS Kulon Progo Daerah Istimewa Yogyakarta - Edhy Sutanta; Catur Iswahyudi (Indonesian Journal of Community Service and Innovation (IJCOSIN), 2023)
The Nyi Ageng Serang Community Information Group (KIM NAS) located in Taruban Kulon, Tuksono, Sentolo, Kulon Progo, Special Region of Yogyakarta (DIY) is an organization that aims to empower and improve people's welfare through information empowerment. KIM NAS' flagship program in 2023 is the development of digital villages. This Community Service (PkM) is carried out as a form of synergy and collaboration between KIM NAS and IST AKPRIND Yogyakarta in the application of science and technology according to the needs of the community. This program includes 2 activities, namely the expansion of wireless internet networks and the provision of information and communication technology (ICT) facilities. PkM activities began with an audition of the KIM NAS management and the Implementation Team, followed by activities for signing the memorandum of understanding and the cooperation agreement, surveys, discussion of programs and activities, preparation, implementation, as well as evaluation and follow-up. The evaluation results of the implementation shows that this activity has achieved the planned target, able to increase the target audience by 3 times, and provide benefits for the management as well as members of the community around the activity location